Mycosis fungoides, lymphomatoid papulosis and Hodgkin's lymphoma in the same patient: Apropos of a possible monoclonal origin - Montserrat Molgó; Leonardo Espinoza-Benavides; Patricio Rojas; Sergio González (Wolters Kluwer Medknow Publications, 2020)
A 59-year-old man with Hodgkin's lymphoma was referred by a hematologist for consultation for cutaneous issues. Physical examination revealed generalized scaling and erythematous scaly patches located in the groin, abdomen, and arms. The biopsy was compatible with mycosis fungoides (MF). At his next medical visit, painful nodules with erythematous halo and scabby surface were noted, and a subsequent biopsy was compatible with lymphomatoid papulosis (LyP). Mycosis fungoides, the most common primary cutaneous T-cell lymphoma, is usually defined in its classic form as a CD4+ non-Hodgkin lymphoma; LyP corresponds to a CD30+ lymphoproliferative disorder; and Hodgkin's lymphoma (HL) constitutes a lymphoid neoplasia characterized by the presence of Reed-Sternberg cells and its variants. Although these entities have been defined independently, evidence suggests the possibility of a common monoclonal origin. To our knowledge, this is the first case of MF, LyP, and HL in a single patient.